2021
DOI: 10.1016/j.neuroimage.2021.118387
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for normal extra-axial cerebrospinal fluid volume in autistic males from middle childhood to adulthood

Abstract: Autism spectrum disorder has long been associated with a variety of organizational and developmental abnormalities in the brain. An increase in extra-axial cerebrospinal fluid volume in autistic individuals between the ages of 6 months and 4 years has been reported in recent studies. Increased extra-axial cerebrospinal fluid volume was predictive of the diagnosis and severity of the autistic symptoms in all of them, irrespective of genetic risk for developing the disorder. In the present study, we explored the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 54 publications
(87 reference statements)
3
21
0
1
Order By: Relevance
“…Також залишається невідомою відповідь на питання про довгострокову клінічну значущість ДРСП і не зовсім зрозуміло, чи є зміни венозного кровотоку тільки причиною, а може й наслідком субарахноїдального розширення у майбутньому [18,[55][56][57][58][59][60]. Таким чином, питання хронічно підвищеного внутрішньочерепного тиску внаслідок порушення венозного відтоку має бути з'ясовано для немовлят із розширенням субарахноїдальних просторів у майбутніх дослідженнях.…”
Section: аналітичні огляди / Analytical Reviewsunclassified
“…Також залишається невідомою відповідь на питання про довгострокову клінічну значущість ДРСП і не зовсім зрозуміло, чи є зміни венозного кровотоку тільки причиною, а може й наслідком субарахноїдального розширення у майбутньому [18,[55][56][57][58][59][60]. Таким чином, питання хронічно підвищеного внутрішньочерепного тиску внаслідок порушення венозного відтоку має бути з'ясовано для немовлят із розширенням субарахноїдальних просторів у майбутніх дослідженнях.…”
Section: аналітичні огляди / Analytical Reviewsunclassified
“…In each of these studies, an increased volume of EA-CSF preceded the onset and severity of the autism diagnosis and symptoms, regardless of genetic risk [ 29 31 ]. Interestingly, in an accelerated, multi-cohort longitudinal study of participants 3–42 years, no difference in EA-CSF volume between the ASD and control groups was found, suggesting that EA-CSF volume may normalize after age 4 in ASD [ 32 ]. Despite this evidence, temporal precedence alone cannot establish causality [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such changes to cortical thickness may occur during synaptic pruning events, such as that during adolescence when there is a well-documented decrease in mean cortical thickness [ 43 45 ]. Such a decrease in cortical thickness could create a deficiency in the subarachnoid space which could then be filled with an increase in the volume of EA-CSF as postulated by Peterson et al [ 32 ]. This relationship between a decrease in mean cortical thickness and an increase in EA-CSF volume has been evidenced in a longitudinal sample of participants 3 to 42 years of age [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a couple of small longitudinal samples individuals that would later go on to be diagnosed with ASD were found to have typically sized brains surrounded by an increased volume of extra-axial CSF (Shen et al, 2018(Shen et al, , 2017. Later attempts to validate and expand on that research however have not found the same patterns, and indicate the association may disappear quickly with increasing age (Peterson et al, 2021)…”
Section: The Ceas In Childrenmentioning
confidence: 99%